A novel plant extract as a biostimulant to recover strawberry plants from iron chlorosis. (8th August 2020) - Saavedra, Teresa; Gama, Florinda; Correia, Pedro José; Da Silva, José Paulo; Miguel, Maria Graça; de Varennes, Amarilis; Pestana, Maribela
Abstract: The traditional agricultural production systems are evolving more toward organic, sustainable or environmental friendly systems and products; however, it is important to keep the yield and the quality of crops. The aim of this work was to evaluate the recovery of iron deficient strawberry plants by foliar spray, using a gramineous plants extract (GE). Bare-root transplants of strawberry ( Fragaria × ananassa Duch. cv "Diamond") were grown in a Hoagland's nutrient solution with iron (Fe10) or without (Fe0). Forty-two days after Fe deprivation, plants grown without iron became chlorotic and GE was applied. Three foliar applications were done, once per week and the regreening was monitored using a SPAD apparatus. After two applications, a rapid but transient regreening was detected in young leaves. Nevertheless, biomass and root/shoot ratio of recovered plants (GE treatment) were similar to chlorotic plants (Fe0 treatment). Phosphorous, Mn and Fe contents were higher in crowns of GE plants at the end of the experiment (67 days). The concentration of organic acids and ferric chelate–reductase (FC-R) activity was also significantly higher in GE treatment. It is possible that the high chelating capacity of the extract was responsible for the Fe internal transport and use.